Manajemen Proyek Perangkat Lunak - Arifin, Furry (ComTech: Computer, Mathematics and Engineering Applications, 2011)
This article contains several things to be controlled by a Project Manager in order to be able to develop a software engineering project plan. The development methodology begins with survey, analysis and engineering in software planning. Establishing a good project team structure is as important as selecting team members who are also experts in their field. Perceiving that the construction and implementation of information technology-based systems are executed using a project management approach, the project manager is then the most responsible officer for the team performance. The project Manager will lead his team to planning and developing information technology projects in accordance with their intended target. There are three fields that must be considered in an information system project, namely: information systems, information technology, and information management.